Clinical-scale, modular manufacturing of tumor-reactive TILs using a closed and automated culture system - Völzke, Christina; Ehrhardt, Lisa; Fischer, Laura; Maul, Peter; Wenzel, Carina; Riabinska, Arina; Criado-Moronati, Elvira; Dienstbier, Mike; Hassel, Jessica; Zhang, Danmei; Haanen, John B.; Handgretinger, Rupert; et al. (Frontiers in Immunology, 2024)
Recent studies have revealed the potential of tumor-infiltrating lymphocytes (TILs) to treat solid tumors effectively and safely. However, the translation of TIL therapy for patients is still hampered by non-standardized and laborious manufacturing procedures that are expensive and produce highly variable cellular products. To address these limitations, the CliniMACS Prodigy® Tumor Reactive T cell (TRT) Process has been developed. The TRT Process allows the automated isolation, transduction, and expansion of tumor-reactive T cells in a clinically compliant and closed system under GMP conditions. The TRT Process can generate tumor-reactive T cells using several methodologies which reflect clinically relevant applications. It can manage an automated Rapid Expansion Protocol (REP) using GMP-compliant reagents to generate a TIL cell product from solid tumors, including melanoma. Additionally, the TRT Process automates the closed selection of CD137-expressing TILs directly from tumor digest followed by the direct expansion of selected cells. Enriched CD137+ TILs could be robustly expanded even when as few as 1x104 TILs were used to seed the REP phase. These data provide proof-of-concept for the isolation and expansion of tumor-reactive T cells from tumor digest in a closed, automated manner in the CliniMACS Prodigy, allowing for an efficient, simple, and reproducible manufacturing of TIL products. The direct selection of CD137+ TILs from tumor digest removes the need for the pre-REP phase, selects for therapeutically relevant cells, and can dramatically shorten the manufacturing time compared to conventional methods.